PENGARUH HAJI TERHADAP POLITIK ISLAM DI INDONESIA (TAHUN 1900-1945) - Eka Yudha Wibowo (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2015)
Hajj is one of the compulsory worship in Islam for every Muslim whohas an ability to carry it out. Pilgrimage has given a new color to the newhistory of the struggle against colonialism in Indonesia, one of which isindicated by the emergence of Islamic political organizations in the period 1900-1945 AD. Hajj activities affect the attitudes and political organization with the emergence of Islamic political organizations were represented by Syarikat Islam then turned into PSII and Permi (Indonesian Muslim Unity Party). This study examines by looking at changes in thinking that occur after the pilgrimage to the effects of the birth of political organization. Changes may include an understanding of the religion and the political ideology thought to unify the spirit of unity of Muslims in this country, to fight for freedom and the struggle against the colonialist.Keywords: Hajj, political organizations, struggle